POWLES' GODGAME: CHARACTERS AND CONCLUSIONS IN THE FRENCH LIEUTENANT'S WOMAN - Reichmann Lemos, Brunilda (Revista Letras, 1983)
This paper analyses the three different endings of Fowles' THE FRENCH LIEUTENANT'S WOMAN and demonstrates that only the third ending is consistent with the development of the female protagonist throughout the novel. We should not forget, on the other hand, that THE FRENCH LIEUTENANT'S WOMAN is a parody of the 19th century novel, therefore Fowles' playfulness at the end is also part of his plan to "ridicule" the role of the victim in the novels of the previous century.